Hubungan Tingkat Stres Tingkat Konsumsi Energi dan Status Gizi Pedagang Wanita Pada Era New Normal di Pasar Umum Gianyar - Widya Adnyani, Ni Made; Ariati, Ni Nengah; Yuni Gumala, Ni Made (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2024)
During the Covid-19 pandemic, there was a new term in society called New Normal. New Normal is an adaptation to new habits, which means carrying out activities by implementing health protocols. One of the things that can be caused by Covid-19 is stress on traders due to a decrease in the number of buyers. 80% of respondents had symptoms of post-traumatic stress due to experiencing or witnessing unpleasant events related to Covid-19. Stress can lead to emotional eating, emotional eating will affect consumption levels and nutritional status of female traders. Female traders must pay attention to stress levels, energy consumption levels, and nutritional status that can be measured with weight and height. The purpose of this study was to determine the relationship between stress levels, energy consumption levels, and the nutritional status of female traders in the new normal era at the Gianyar public market. This type of observational research with a cross sectional design using a purposive sampling technique with a total of 94 people. Data collected by interview method and taking measurements. Data is presented with frequency tables and cross tables. The results of the Rank Spearman test showed that there was no significant relationship between stress levels and energy consumption levels (p= 0,215) and there was a significant relationship between energy consumption levels and nutritional status (p= 0,001).